1995
DOI: 10.1074/jbc.270.22.13036
|View full text |Cite
|
Sign up to set email alerts
|

The PPZ Protein Phosphatases Are Important Determinants of Salt Tolerance in Yeast Cells

Abstract: Protein phosphatases PPZ1 and PPZ2 represent a novel form of Ser/Thr phosphatases structurally related to type 1 phosphatases and characterized by an unusual amino-terminal region. We have found that the deletion of PPZ1 gene results in increased tolerance to Na+ and Li+ cations. Simultaneous deletion of PPZ2 gene results in an additional increase in salt tolerance. After exposure to high concentration of Li+, the intracellular content of the cation was markedly decreased in ppz1 delta ppz2 delta mutants when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
155
2
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(162 citation statements)
references
References 31 publications
4
155
2
1
Order By: Relevance
“…It is known that S. cerevisiae ppz1 tolerates saline treatment, but we found no significant differences between the parental and mutated C. albicans strains in the presence of NaCl. It was previously suggested that the tolerance to NaCl (and LiCl) of the S. cerevisiae mutant can be explained by the overexpression of the ENA1 sodium transporter (Posas et al, 1995;Ruiz et al, 2003). Sequence comparisons revealed that in C. albicans the orf19.6070 protein is an ENA1 orthologue; however, its function and regulation are not known at the moment.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…It is known that S. cerevisiae ppz1 tolerates saline treatment, but we found no significant differences between the parental and mutated C. albicans strains in the presence of NaCl. It was previously suggested that the tolerance to NaCl (and LiCl) of the S. cerevisiae mutant can be explained by the overexpression of the ENA1 sodium transporter (Posas et al, 1995;Ruiz et al, 2003). Sequence comparisons revealed that in C. albicans the orf19.6070 protein is an ENA1 orthologue; however, its function and regulation are not known at the moment.…”
Section: Discussionmentioning
confidence: 97%
“…We found that the null mutant was tolerant to LiCl, and was sensitive to KCl. According to these properties it behaves like the S. cerevisiae ppz1 mutant (Posas et al, 1995;Ruiz et al, 2003;Yenush et al, 2002). However, there was a clear-cut difference between the two mutants when sensitivity to NaCl was tested.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations